1045. Longitudinal Evaluation of the QuantiFERON-TB Gold Plus Assay in Hospitalized COVID-19 Patients with a First Indeterminate Result: Resolution of Inflammation and Restoration T-lymphocyte Counts and Interferon-gamma Production. (15th December 2022) - Imeneo, Alessandra; Alessio, Grazia; Lorenzo, Andrea Di; Campogiani, Laura; Lodi, Alessandra; Barreca, Filippo; Crea, Angela; Vitale, Pietro; Spalliera, Ilaria; Compagno, Mirko; Coppola, Luigi; Malagnino, Vincenzo; et al.
Abstract: Background: Several studies reported an increased rate of indeterminate QuantiFERON-TB Gold Plus (QFT-P) assay results in patients with severe Coronavirus Disease (COVID)-19. Methods: Aim of the study was to longitudinally evaluate QFT-P responses in patients who survived COVID-19, with a previous indeterminate result. Results: We observed 223 patients with an indeterminate QFT-P assay among 949 patients hospitalized because of COVID-19 (23, 5%) during 2020 and 2021. 36 patients among those with an indeterminate QFT-P assay were enrolled for reassessing the test. In 12 patients peripheral blood lymphocyte subsets were also reassessed. Considering disease severity, 30 were classified as severe and 6 as non-severe. Median age was 57, 5 (interquartile range [IQR]: 49, 5-63, 8), with a prevalence of male sex (M/F: 24/12); median Charlson Comorbidity Index was 2 (IQR: 1-3). The second QFT-P assay was performed after at least 1 month from the first assay (median time 7 months, IQR: 5-12 months). All QFT-P assays gave a determined result: 2 positive (5.5%) and 34 negatives (94, 4%). A statistically significant difference was observed after comparing the laboratory parameters at the time of the first and the second QFT-P assay: the absolute counts of total lymphocyte, total CD3+, CD4+ and CD8+ T-lymphocytes were significantly increased (p< 0.001) while neutrophil absolute counts, neutrophil to lymphocyte (N/L) ratio, D-dimer, fibrinogen, ferritin, C-reactive protein (CRP) were significantly reduced (p< 0.0001). Concerning the QFT-P assay, interferon gamma (INF-γ) production in the Mitogen-Nil, TB1-Nil and TB2-Nil conditions were significantly increased (p< 0.0001; p=0.0019; p=0.0205, respectively) (Table 1 and Figure 1). Conclusion: Once the acute phase of COVID-19 is resolved, inflammatory markers and peripheral blood leucocyte counts tend to normalize with an effective INF-γ production after specific and nonspecific stimulation. All the 36 QFT-P showed a determinate result. Moreover, we observed 2 positive QFT-P assay, supporting the importance of retesting patients with indeterminate result to identify latent tuberculosis infection and monitor patients for possible reactivation because of the immune-suppression associated with COVID-19. Disclosures: All Authors : No reported disclosures.